Effects of the NEDD8-Activating Enzyme Inhibitor MLN4924 on Lytic Reactivation of Kaposi's Sarcoma-Associated Herpesvirus - Chang, Pey-Jium; Chen, Lee-Wen; Chen, Li-Yu; Hung, Chien-Hui; Shih, Ying-Ju; Wang, Shie-Shan (Journal of virology, 2017)
The switch of Kaposi's sarcoma-associated herpesvirus (KSHV) from latency to lytic replication is a key event for viral dissemination and pathogenesis. MLN4924, a novel neddylation inhibitor, reportedly causes the onset of KSHV reactivation but impairs later phases of the viral lytic program in infected cells. Thus far, the molecular mechanism involved in the modulation of the KSHV lytic cycle by MLN4924 is not yet fully understood. Here, we confirmed that treatment of different KSHV-infected primary effusion lymphoma (PEL) cell lines with MLN4924 substantially induces viral lytic protein expression. Due to the key role of the virally encoded ORF50 protein in the latent-to-lytic switch, we investigated its transcriptional regulation by MLN4924. We found that MLN4924 activates the ORF50 promoter (ORF50p) in KSHV-positive cells (but not in KSHV-negative cells), and the RBP-Jκ-binding elements within the promoter are critically required for MLN4924 responsiveness. In KSHV-negative cells, reactivation of the ORF50 promoter by MLN4924 requires the presence of the latency-associated nuclear antigen (LANA). Under such a condition, LANA acts as a repressor to block the ORF50p activity, whereas MLN4924 treatment relieves LANA-mediated repression. Importantly, we showed that LANA is a neddylated protein and can be deneddylated by MLN4924. On the other hand, we revealed that MLN4924 exhibits concentration-dependent biphasic effects on 12- O -tetradecanoylphorbol-13-acetate (TPA)- or sodium butyrate (SB)-induced viral reactivation in PEL cell lines. In other words, low concentrations of MLN4924 promote activation of TPA- or SB-mediated viral reactivation, whereas high concentrations of MLN4924, conversely, inhibit the progression of TPA- or SB-mediated viral lytic program. IMPORTANCE MLN4924 is a neddylation (NEDD8 modification) inhibitor, which currently acts as an anti-cancer drug in clinical trials. Although MLN4924 has been reported to trigger KSHV reactivation, many aspects regarding the action of MLN4924 in regulating the KSHV lytic cycle are not fully understood. Since the KSHV ORF50 protein is the key regulator of viral lytic reactivation, we focus on its transcriptional regulation by MLN4924. We here show that activation of the ORF50 gene by MLN4924 involves the relief of LANA-mediated transcriptional repression. Importantly, we find that LANA is a neddylated protein. To our knowledge, this is the first report showing that neddylation occurs in viral proteins. Additionally, we provide evidence that different concentrations of MLN4924 have opposite effects on TPA-mediated or SB-mediated KSHV lytic cycle activation. Therefore, in clinical application, we propose that MLN4924 needs to be used with caution in combination therapy to treat KSHV-positive subjects.